The Evolution of Empathy and Women’s Precarious Leadership Appointments - Vongas, John G.; Al Hajj, Raghid (Frontiers in Psychology, 2015)
Glass cliffs describe situations in which women are promoted to executive roles in declining organizations. To explain them, some authors suggest that people tend to “think crisis-think female.” However, the root cause of this association remains elusive. Using several subfields of evolutionary theory, we argue that biology and culture have shaped the perception of women as being more empathic than men and, consequently, as capable of quelling certain crises. Some crises are more intense than others and, whereas some brew within organizations, others originate from the external environment. We therefore propose that women will be selected to lead whenever a crisis is minimal to moderate and stems primarily from within the organization. Men, on the other hand, will be chosen as leaders whenever the crisis threatens the very existence of the firm and its source is an external threat. Leadership is a highly stressful experience, and even more so when leaders must scale glass cliffs. It is imperative that we understand what gives rise to them not only because they place women and potentially other minorities in positions where the likelihood of failure is high, but also because they help propagate stereotypes that undermine their true leadership ability.